A lithium battery single-ion conductor polymer electrolyte and a preparation method thereof
Patent Information
- Application Number
- CN202410249131.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-05
AI Technical Summary
目前单离子导体聚合物电解质存在机械性能较差,电池容量较低,高倍率循环能力较差的问题,为此本发明提供了一种具备高能量密度,高机械强度,高倍率循环的锂电池单离子导体聚合物电解质,该电解质成本便宜,性能优良,极具商业化潜力
[0021]相对于现有技术而言,本发明的有益技术效果是:(1)本发明中设计的单离子导体聚合物电解质PVDF-BSFE选择了PVDF-CTFE,PVDF-HFP等PVDF共聚物作为聚合物主链,该主链相比于PVDF材料拥有更好的吸电子能力;(2)嫁接的阴离子基团具有更好的吸电子能力,可以大幅提高锂离子迁移数;(3)本发明的单离子导体聚合物电解质材料以PVDF共聚物为基底制备,除制备隔膜以外,也可以作为电池粘结剂材料使用。
Smart Images

Figure CN117913456B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, specifically to a single-ion conductor polymer electrolyte for lithium batteries and its preparation method. Background Technology
[0002] Lithium metal batteries are rechargeable batteries using metallic lithium as the anode and are considered one of the most promising high-energy-density energy storage devices. However, lithium dendrites grow during charging and discharging, which can puncture the separator and cause a short circuit, severely hindering their practical application. To address lithium battery safety issues, one current solution is the development of solid-state electrolytes. However, solid-state electrolytes, due to their low lithium-ion transference number (typically less than 0.5), exhibit significant concentration polarization, making it difficult to suppress lithium dendrite growth and posing a considerable safety hazard.
[0003] Single-ion conductor polymer electrolytes, due to their near-one lithium-ion transference number, can effectively reduce concentration polarization, thereby significantly suppressing lithium dendrite growth and potentially enabling high-energy-density, long-life, and high-safety lithium batteries. Currently, single-ion conductor polymer electrolytes suffer from poor mechanical properties, low battery capacity, and poor high-rate cycling performance. Therefore, this invention provides a single-ion conductor polymer electrolyte for lithium batteries with high energy density, high mechanical strength, and high-rate cycling performance. This electrolyte is inexpensive, has excellent performance, and possesses significant commercial potential. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a single-ion conductor polymer electrolyte for lithium batteries and its preparation method. Lithium benzenesulfonate anionic groups are grafted onto the polymer backbone of PVDF and its copolymers via monosulfide bonds to obtain the single-ion conductor polymer electrolyte PVDF-BSFE. Due to its highly conjugated structure, lithium benzenesulfonate possesses strong electron-withdrawing capabilities, facilitating the dissociation and migration of lithium ions. The anions are fixed on the polymer backbone, inhibiting anion migration and significantly improving the battery's cycle life and rate capability.
[0005] The preparation method of the polymer electrolyte for lithium-ion batteries includes the following steps:
[0006] Step (1): Dissolve p-aminobenzenesulfonic acid and anhydrous sodium carbonate in pure water and then cool to 15°C;
[0007] Step (2): Dissolve sodium nitrite in purified water;
[0008] Step (3): Add the solution obtained in step (2) to the solution obtained in step (1), then slowly add hydrochloric acid and crushed ice, stir under low temperature conditions to generate a diazo compound;
[0009] Step (4): Add sodium sulfide nonahydrate and sulfur powder to water, and add sodium hydroxide solution to form sodium disulfide solution;
[0010] Step (5): Add the diazo compound obtained in step (3) to the sodium disulfide solution obtained in step (4) and stir at low temperature to obtain sodium 4,4'-dimercaptodibenzenesulfonate.
[0011] Step (6): Dissolve the sodium 4,4'-dimercaptodiphenylsulfonate obtained in step (5) in water and convert the sodium 4,4'-dimercaptodiphenylsulfonate into 4,4'-dimercaptodiphenylsulfonic acid through an acidic cation exchange resin.
[0012] Step (7): Dissolve the 4,4'-dimercaptodibenzenesulfonic acid obtained in step (6) in methanol, add water and reducing agent, and stir to generate p-mercaptobenzenesulfonic acid;
[0013] Step (8) uses a strong base containing lithium ions to convert the mercapto group and sulfonic acid of the p-mercaptobenzenesulfonic acid obtained in step (7) into the corresponding lithium salts, namely lithium sulfide and lithium benzenesulfonate.
[0014] Step (9): The lithium salt obtained in step (8) is added to the solution of polyvinylidene fluoride (PVDF) and its copolymer to obtain lithium benzenesulfonate-grafted PVDF copolymer, i.e., single-ion conductor polymer.
[0015] Step (10): Dissolve the single-ion conductor polymer obtained in step (9) in a solvent to prepare a single-ion conductor polymer solution;
[0016] Step (11): The single-ion conductor polymer solution is coated onto the substrate and dried to obtain the single-ion conductor polymer electrolyte.
[0017] The strong base containing lithium ions includes one of LiOH, Li2CO3, lithium methoxide, lithium ethanol, lithium tert-butoxide, butyllithium, lithium hexamethyldisilamide, lithium amino, and lithium 2,2,6,6-tetramethylpiperidine, and the reducing agent is one of zinc-acetic acid, sodium borohydride, and triphenylphosphine, preferably triphenylphosphine.
[0018] Further, the solvent of the PVDF and its copolymer solution includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, acetone, THF, cyclohexanone, methyl isobutyl ketone, ethyl acetate, butyl acetate, butyl butyrate, hexyl hexanoate, ethylene glycol methyl ether, and diisobutyl ketone; the solvent in step (10) includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, butanone, and acetone.
[0019] Furthermore, by adding lithium salt in step (10), a solid electrolyte film can be prepared. The added lithium salt includes one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalateborate), and lithium bis(fluorooxalateborate).
[0020] The lithium battery single-ion conductor polymer electrolyte prepared by the above method grafts lithium benzenesulfonate onto PVDF and its copolymers through monosulfide bonds. PVDF and its copolymers include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene PVDF-CTFE, and polyvinylidene fluoride-chlorotrifluoroethylene PVDF-TrFE.
[0021] Compared with the prior art, the beneficial technical effects of the present invention are: (1) The single-ion conductor polymer electrolyte PVDF-BSFE designed in the present invention selects PVDF-CTFE, PVDF-HFP and other PVDF copolymers as the polymer backbone, which has better electron absorption capacity than PVDF materials; (2) The grafted anionic groups have better electron absorption capacity, which can greatly improve the lithium ion transference number; (3) The single-ion conductor polymer electrolyte material of the present invention is prepared with PVDF copolymer as the base, and can be used as a battery binder material in addition to preparing separators. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a flowchart of the preparation method of PVDF-BSFE;
[0024] Figure 2 This is a schematic diagram of the chemical structure of PVDF-BSFE.
[0025] Figure 3 Phase diagram and elemental distribution characterization of PVDF-BSFE electrolyte;
[0026] Figure 4 Infrared spectra of PVDF-BSFE and PVDF-CTFE materials;
[0027] Figure 5 Cycle profiles of batteries assembled with PVDF-BSFE separators and commercial PE separators;
[0028] Figure 6 The lithium-ion transference number of the PVDF-BSFE separator;
[0029] Figure 7 A comparison of lithium-ion transference numbers between PVDF-BSFE-based solid electrolytes and PVDF-based solid electrolytes;
[0030] Figure 8 A comparison of battery cycle curves between PVDF-BSFE-based solid electrolyte and PVDF-based solid electrolyte. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] The lithium benzenesulfonate single-ion conductor polymer electrolyte material provided by this invention can not only be used to prepare separators, but also as a binder in the preparation of lithium-ion batteries.
[0033] The lithium benzenesulfonate single-ion conductor polymer electrolyte material provided by the present invention comprises the following weight composition: 80-95 parts of PVDF and its copolymers, and 5-20 parts of lithium benzenesulfonate salt.
[0034] The following is a specific example:
[0035] Example 1
[0036] The specific steps for preparing lithium benzenesulfonate single-ion conductor polymer electrolyte are as follows:
[0037] (1) Dissolve 0.25 mol of p-aminobenzenesulfonic acid and 0.13 mol of anhydrous sodium carbonate in 500 ml of purified water, and then cool to 15 °C;
[0038] (2) Dissolve 0.25 mol sodium nitrite in 50 ml of purified water;
[0039] (3) Add the solution obtained in step (2) to the solution obtained in step (1), and then slowly add 52.5 ml of hydrochloric acid and 400 g of crushed ice. Stir under low temperature conditions to generate diazo compound.
[0040] (4) Add 0.27 mol sodium sulfide nonahydrate and 0.27 mol sulfur powder to 75 ml of water, and add 0.1 mol / L sodium hydroxide solution to form sodium disulfide solution;
[0041] (5) Add the diazo compound obtained in step (3) to the sodium disulfide solution obtained in step (4), stir for 2 hours below 5°C, and after the nitrogen gas is released, adjust the pH to 2, then filter the elemental sulfur and heat it to release hydrogen sulfide, then adjust the pH of the solution to neutral, filter and cool to obtain sodium 4,4'-dimercaptodibenzenesulfonate.
[0042] (6) Dissolve the sodium 4,4'-dimercaptodibenzenesulfonate obtained in step (5) in water and convert the sodium 4,4'-dimercaptodibenzenesulfonate into 4,4'-dimercaptodibenzenesulfonic acid through an acidic cation exchange resin.
[0043] (7) Dissolve the 4,4'-dimercaptodibenzenesulfonic acid obtained in step (6) in 50 ml of methanol, add 200 ml of water and 0.1 mol of triphenylphosphine, and stir to generate a p-mercaptobenzenesulfonic acid solution;
[0044] (8) Add 0.1 mol of lithium hydroxide to the p-mercaptobenzenesulfonic acid solution obtained in step (7) to convert the mercapto group and sulfonic acid into the corresponding lithium salts, namely lithium sulfide and lithium benzenesulfonate.
[0045] (9) Add the lithium salt obtained in step (8) to the solution of PVDF and its copolymer to obtain lithium benzenesulfonate grafted PVDF copolymer, namely lithium benzenesulfonate single ion conductor polymer.
[0046] (10) Dissolve the lithium benzenesulfonate-grafted PVDF copolymer obtained in step (9) in methyl ethyl ketone at a ratio of approximately 1 g: 20 ml, then heat to 80-120 °C and stir uniformly for 24 hours to prepare a single-ion conductor polymer solution using a scraping method.
[0047] (11) The prepared single-ion conductor polymer solution was placed in a vacuum oven at 40°C for 24 hours to obtain lithium benzenesulfonate single-ion conductor polymer electrolyte.
[0048] (12) The obtained single-ion conductor polymer electrolyte was immersed in an organic solvent of ethylene carbonate EC: dimethyl carbonate DMC = 1:1 for 24 hours;
[0049] (13) Use the separator obtained in step (12) to assemble a lithium battery and perform the corresponding tests.
[0050] Example 2
[0051] By using lithium benzenesulfonate single-ion conductor polymer electrolyte to completely replace the traditional PVDF binder in the production of polymer solid electrolyte, the lithium-ion transference number of the battery is increased, thereby improving the performance of solid lithium batteries.
[0052] (1) The synthesis steps of lithium benzenesulfonate single-ion conductor polymer are the same as in Example 1;
[0053] (2) Add 60 parts of lithium benzenesulfonate single-ion conductor polymer to a certain amount of N-methylpyrrolidone (NMP) solvent, heat and stir until uniform;
[0054] (3) Transfer the solution prepared in step (2) into a glove box, add 40 parts of lithium trifluoromethanesulfonylimide, and then stir for 24 hours;
[0055] (4) The solution prepared in step (3) is coated onto the copper foil by a scraping method;
[0056] (5) Place the copper foil in a vacuum drying oven at 60°C for 24 hours to obtain a dried single-ion conductor polymer electrolyte.
[0057] Example 3
[0058] In Example 3, a commercial PE separator was used to prepare the battery. The major difference from Example 1 is that lithium battery electrolyte was added during the battery preparation process.
[0059] Example 4
[0060] In this embodiment, pure PVDF material is selected as the binder to prepare the polymer solid electrolyte. The specific steps are as follows:
[0061] (1) Add 60 parts of PVDF material to a certain amount of NMP solvent and stir until homogeneous;
[0062] (2) Transfer the solution prepared in step (1) into a glove box, add 40 parts of lithium trifluoromethanesulfonylimide, and then stir for 24 hours;
[0063] (3) The solution prepared in step (2) is coated onto the copper foil by a scraping method;
[0064] (4) Place the copper foil in a vacuum drying oven at 60°C for 24 hours to obtain a dried single-ion conductor polymer electrolyte.
[0065] Figure 1 This is a flow chart of the preparation method of lithium benzenesulfonate single-ion conductor polymer electrolyte (PVDF-BSFE). Figure 2 This is a schematic diagram of the chemical structure of PVDF-BSFE. It can be seen that replacing the cl atom of PVDF-CTFE material with lithium benzenesulfonate forms the polymer electrolyte material synthesized in this invention.
[0066] Figure 3 The images show the SEM morphology and EDS characterization (elemental distribution characterization) of the PVDF-BSFE separator. The separator has a porous structure, facilitating lithium-ion transport. EDS characterization also reveals the presence of S, F, and O elements in the separator, indicating successful grafting of lithium benzenesulfonate anions onto the material.
[0067] Figure 4 Infrared characterization of PVDF-BSFE material was performed. Compared with the polymer backbone without lithium benzenesulfonate anion grafting, the peak value at 763 wavenumber disappeared, indicating that the C-Cl bond disappeared in the synthesized material. This further proves that the lithium benzenesulfonate anion replaced the Cl atom, which is consistent with the expected synthesized structure.
[0068] Figure 5 The cycle performance of batteries assembled with PVDF-BSFE separators and commercial PE separators was characterized. It can be seen that the separator designed in this invention exhibits superior charge and discharge performance compared to commercial separators, and has great development potential.
[0069] Figure 6 For the lithium-ion transference number test of the PVDF-BSFE separator, the lithium-ion battery separator of the present invention achieved a transference number of 0.92, which has excellent performance in suppressing anion transport, thus exhibiting better lithium-ion transport performance.
[0070] Figure 7 The lithium-ion transference number of solid-state batteries prepared by a novel binder obtained by blending PVDF-BSFE with PVDF materials was tested. Compared with commercial PVDF binders, the lithium-ion transference number was significantly increased from 0.16 to 0.55, demonstrating excellent electrochemical performance.
[0071] Figure 8 A battery cycle comparison between PVDF-BSFE-based solid electrolyte and PVDF-based polymer solid electrolyte shows that the material of this invention exhibits superior performance compared to PVDF material. The PVDF-based solid electrolyte battery has a capacity of approximately 85 mAh / g at 0.5C, while the PVDF-BSFE-based solid electrolyte has a capacity of approximately 120 mAh / g, demonstrating superior performance.
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.
Claims
1. A method for preparing a single-ion conductor polymer electrolyte for lithium batteries, characterized in that, The method includes the following steps: Step (1): Dissolve p-aminobenzenesulfonic acid and anhydrous sodium carbonate in pure water and then cool to 15°C; Step (2): Dissolve sodium nitrite in purified water; Step (3): Add the solution obtained in step (2) to the solution obtained in step (1), then slowly add hydrochloric acid and crushed ice, stir under low temperature conditions to generate a diazo compound; Step (4): Add sodium sulfide nonahydrate and sulfur powder to water, and add sodium hydroxide solution to form sodium disulfide solution; Step (5): Add the diazo compound obtained in step (3) to the sodium disulfide solution obtained in step (4) and stir at low temperature to obtain sodium 4,4'-dimercaptodibenzenesulfonate. Step (6): Dissolve the sodium 4,4'-dimercaptodiphenylsulfonate obtained in step (5) in water and convert the sodium 4,4'-dimercaptodiphenylsulfonate into 4,4'-dimercaptodiphenylsulfonic acid through an acidic cation exchange resin. Step (7): Dissolve the 4,4'-dimercaptodibenzenesulfonic acid obtained in step (6) in methanol, add water and reducing agent, and stir to generate p-mercaptobenzenesulfonic acid; Step (8) uses a strong base containing lithium ions to convert the mercapto group and sulfonic acid of the p-mercaptobenzenesulfonic acid obtained in step (7) into the corresponding lithium salts, namely lithium sulfide and lithium benzenesulfonate. Step (9): The lithium salt obtained in step (8) is added to the solution of polyvinylidene fluoride (PVDF) and its copolymer to obtain lithium benzenesulfonate-grafted PVDF copolymer, i.e., single-ion conductor polymer. Step (10): Dissolve the single-ion conductor polymer obtained in step (9) in a solvent to prepare a single-ion conductor polymer solution; Step (11): The single-ion conductor polymer solution is coated onto the substrate and dried to obtain the single-ion conductor polymer electrolyte.
2. The method according to claim 1, characterized in that, Strong bases containing lithium ions include one of LiOH, Li2CO3, lithium methoxide, lithium ethanol, lithium tert-butoxide, butyllithium, lithium hexamethyldisilamide, lithium amino, and lithium 2,2,6,6-tetramethylpiperidine.
3. The method according to claim 1, characterized in that, The reducing agent is one of zinc-acetic acid, sodium borohydride, and triphenylphosphine.
4. The method according to claim 1, characterized in that, The solvents for PVDF and its copolymer solutions include one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, acetone, THF, cyclohexanone, methyl isobutyl ketone, ethyl acetate, butyl acetate, butyl butyrate, hexyl hexanoate, ethylene glycol methyl ether, and diisobutyl ketone.
5. The method according to claim 1, characterized in that, The solvent in step (10) includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, butanone, and acetone.
6. The method according to claim 1, characterized in that, In step (10), lithium salt is added to prepare a solid electrolyte film. The added lithium salt includes one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalateborate), and lithium bis(fluorooxalateborate).
7. A lithium-ion battery single-ion conductor polymer electrolyte, prepared by the method according to any one of claims 1-6, characterized in that, Lithium benzenesulfonate is grafted onto PVDF and its copolymers via monosulfide bonds. PVDF and its copolymers include one or more of PVDF, PVDF-HFP, PVDF-CTFE, and PVDF-TrFE.
Citation Information
Patent Citations
Lithium ion organic positive electrode material, preparation method and application
CN111326725A
Single-ion conductive polymer electrolyte and preparation method and application thereof
CN112382788A
